The effectiveness and transferability of a block- mode discipline-specific academic language development program. 'A practice report' - Joseph Yeo; Gemma O'Donoghue (Student success, 2023)
To address the demands from their courses, students with insufficient language proficiency who cannot attend the standard subject-specific academic language development program are directed to an alternative discipline-specific program - the Language Development Tutorial in Block mode, at the University of Technology Sydney. This practice report evaluates the effectiveness of the alternative program, and the transferability of disciplinary learnings to a subject and assessment level. The findings reveal that most students were satisfied with the program and agreed that it had helped to improve their confidence, discipline-specific language and literacy skills, subject content understanding, and ability to complete their assessments. Students who completed the program were also more likely to achieve higher subject results than those who did not attend/complete it. The findings reinforce the need to provide alternative discipline-specific support where subject-specific support is not viable. More in-depth investigation in future iterations will improve the program's impact.